Lymphadenectomy for Low-Risk Endometrial Cancer Based on Preoperative and Intraoperative Assessments. Issue 4 (1st April 2009) - Kang, Woo Dae; Kim, Cheol Hong; Cho, Moon Kyoung; Kim, Jong Woon; Kim, Yoon Ha; Choi, Ho Sun; Kim, Seok Mo
Abstract : Introduction: The aim of this study was to ascertain whether lymphadenectomy is necessary when endometrial cancer is considered low risk based on preoperative and intraoperative assessments. Methods: Between 2000 and 2004, a total of 122 patients with low-risk endometrial cancer who underwent preoperative endometrial sampling and magnetic resonance imaging (MRI) were treated surgically. All 122 patients were considered eligible for the study if they fulfilled the following criteria: ( a ) grade 1 or 2 endometrioid corpus cancer by endometrial sampling, ( b ) no lymphadenopathy by MRI, ( c ) myometrial invasion of 50% or less by MRI, and ( d ) no intraoperative evidence of macroscopic extrauterine spread. We divided the 122 patients into 2 groups (the total abdominal hysterectomy and bilateral salpingo-oophorectomy [TH/bilateral salpingo-oophorectomy] with lymphadenectomy [THND group, n = 64] and the TH/bilateral salpingo-oophorectomy without lymphadenectomy [TH group, n = 58]). Results: The concordance rate between preoperative and postoperative grades was 92.6% (113/122, κ = 0.805). Evaluation of the depth of myometrial invasion with MRI had an accuracy of 95.1% (116/122) for ruling out deep myometrial invasion. In the THND group, the operative time, the hospital stay, the estimated blood loss during surgery, and the incidence of perioperative complications were significantly higher than those in the TH group. The 5-year progression-free survival rates were similar (96.9% in the THND group and 98.3% in the TH group). Conclusions: The present findings suggest that MRI and office endometrial sampling may accurately categorize patients into low- or high-risk groups. Lymphadenectomy should be limited to patients with high-risk endometrial cancer.